2016
DOI: 10.17985/ijare.45901
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Good Student Teachers in Writing Skill: The Impact of Different Task Variance on EFL Writing Proficiency

Abstract: The purpose of this experimental study was (M = 72.57, SE = 1.81) than Group II on student's writing proficiency (M = 56.50, SE = 2.16). This difference is significant (t (58) = 5.70; p < 0.05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Among the four skills of English, Richardson and Morgan (2003) state that "writing may be the most complex communication process within the communicative arts" (as cited in Marzulina & Saputra, 2015, p.3). Therefore, writing is a part of language skills and it becomes one of Available online at http://jurnal.radenfatah.ac.id/index.php/edukasi important skills in English (Astrid et al, 2019;Erlina et al, 2019;Makmur et al, 2016;Prasojo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the four skills of English, Richardson and Morgan (2003) state that "writing may be the most complex communication process within the communicative arts" (as cited in Marzulina & Saputra, 2015, p.3). Therefore, writing is a part of language skills and it becomes one of Available online at http://jurnal.radenfatah.ac.id/index.php/edukasi important skills in English (Astrid et al, 2019;Erlina et al, 2019;Makmur et al, 2016;Prasojo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that English writing remains a challenging task that causes problems for EFL students (Astrid et al, 2019;De Silva, 2015;Hanh & Tinh, 2022;Wang, 2015;Zaghlool, 2020). A large number of EFL college students encounter difficulties in making their language work in a paragraph, such as constructing a grammatically correct sentence, or choosing appropriate vocabulary to link and convey their ideas (Mukminin et al, 2015;Makmur et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been acknowledged that English has been already become an international language. It means that English is a means of communication that is used internationally by people to communicate with others to transfer ideas, thoughts, feelings, attitudes, or messages (Abrar et al, 2018;Erlina et al, 2019;Habibi et al, 2019;Makmur, Mukminin, Ismiyanti, & Verawati, 2016;Marzulina et al, 2019). One of the essential skills is listening (Maimunah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%